Effect of iron supplementation in children with breath holding spells. (1st June 2017) - Jain, Rahul; Omanakuttan, Divin; Singh, Amitabh; Jajoo, Mamta
Abstract : Aim: The aim of this study was to analyse the effect of iron supplementation in children with breath holding spells, irrespective of their iron status and study the factors associated with the response. Methods: This was a prospective interventional study. Study population comprised of patients aged 6–36 months, attending a paediatric outpatient department with recurrent episodes (more than three in last 4 weeks) of breath holding spells. Children with loss of consciousness or convulsive movements associated with breath holding spells were considered as severe. After baseline investigations, all enrolled patients were given elemental iron at the dose of 3 mg/kg/day as a single daily dose. Four weekly follow‐ups were done until 3 months after initiation of the intervention. At 12 weeks, investigations were repeated and outcome assessed for remission or decrease in severity of breath holding episodes. Results: A total of 100 children with breath holding spells received iron supplementation. Almost 73% of children showed complete response, with another 23% showing greater than 50% reduction in frequency. Frequency of spells at diagnosis and intolerance to oral iron were significantly associated with poor response to iron supplementation. Other factors such as age at onset, age at presentation, severity of spells, anaemia and serum iron parameters had no significant association with the response. Of the 27 children without iron deficiency (serum ferritin ≥ 30 µg/L), 77.7% responded completely to iron supplementation, similar to the iron‐deficient group. Conclusions: Iron supplementation is effective in the management of breath holding spells. Non‐anaemic and iron‐replete children with breath holding spells also respond well to iron supplementation.